2010
DOI: 10.1021/ol101451s
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereo- and Enantioselective Synthesis of Monodifferentiated syn-1,2-Diol Derivatives through Asymmetric Transfer Hydrogenation via Dynamic Kinetic Resolution

Abstract: The first enantio- and diastereoselective approach to alpha-alkoxy-substituted syn-beta-hydroxyesters through highly efficient catalytic asymmetric transfer hydrogenation via dynamic kinetic resolution reactions from the corresponding racemic beta-ketoesters is described. In this atom-economical process, two contiguous stereogenic centers are generated simultaneously with an excellent diastereoselectivity (up to 99/1) and enantioselectivity (up to 99%), allowing a rapid access to a wide variety of aromatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…However, most of the reported synthetic approaches to such units suffered from no differentiation of the two hydroxyl groups. In this context, we envisaged, in collaboration with Hoffmann‐La Roche, that the combination of DKR process with the ATH of racemic α‐alkoxy‐substituted β‐keto esters could provide a novel route to access stereodefined monodifferentiated 1,2‐diols units 60…”
Section: Asymmetric Transfer Hydrogenation (Ath)mentioning
confidence: 99%
“…However, most of the reported synthetic approaches to such units suffered from no differentiation of the two hydroxyl groups. In this context, we envisaged, in collaboration with Hoffmann‐La Roche, that the combination of DKR process with the ATH of racemic α‐alkoxy‐substituted β‐keto esters could provide a novel route to access stereodefined monodifferentiated 1,2‐diols units 60…”
Section: Asymmetric Transfer Hydrogenation (Ath)mentioning
confidence: 99%
“…In the same year Ratovelomanana-Vidal et al reported a DKR of related a-alkoxy-b-ketoesters based on Noyori's catalyst. 11 A number of ruthenium complexes were screened at 30 1C using 1.4 equiv. of a 5 : 2 formic acid-triethylamine mixture as a hydrogen source.…”
Section: Transition Metal-catalysed Dkrmentioning
confidence: 99%
“…Continuing our ongoing research toward the synthesis of relevant biologically active compounds by transition‐metal‐catalyzed asymmetric reduction,7 in a preliminary communication,8 we described a highly efficient procedure for ATH of prochiral α‐alkoxy‐β‐ketoesters coupled with a DKR process under mild reaction conditions with HCO 2 H/NEt 3 as the hydrogen source and well‐defined, commercially available chiral catalyst Ru II –TsDPEN. In this earlier effort, we demonstrated that easily accessible racemic aryl α‐alkoxy‐β‐ketoesters could be efficiently transformed to the corresponding monodifferentiated 1,2‐diols with almost perfect enantioselectivity (enantiomeric excess ( ee ) up to 99 %) and excellent diastereoselectivity (diastereomeric ratio (d.r.)…”
Section: Introductionmentioning
confidence: 99%